(untitled) (European Journal of Pure and Applied Mathematics, 2009)
Â This effort derived a mathematical programming model, which is a hybrid from set covering model of discrete location approaches and center of gravity method of continuous location models, for location of blood banks among hospitals or clinics, rather than blood bank layout in health care institutions. It is initially unknown the number of blood banks will be located within capacity, their geographical locations and their covering area. The solution of the model enlightens the initial darkness in a multiobjective view. The objectives, which are handled via binary nonlinear goal programming, are minimizitation of total fixed cost of location blood banks, total traveled distance between the blood banks and hospitals and an inequality index as a fairness mechanism for the distances. A hypothetical numerical example is solved using MS Excel as a powerful spreadsheet tool. The recipe, which is an application of medical operations research, may be a useful tool for health care policy makers.